Psychometric Properties of a Measure Assessing Attitudes and Norms as Determinants of Intention to Use Oral Contraceptives - Jongwon Lee, PhD, RN; Mauricio Carvallo, PhD; Taehun Lee, PhD (Elsevier, 2015)
Purpose: Asian immigrant and Asian American women are less likely to use oral contraceptives (OCs) and tend to rely on low-efficacy methods of contraception. This contraceptive pattern remains poorly understood, in part, because no theory-driven measurement exists to assess psychosocial determinants essential in explaining behaviors related to OC use in this population. The current study aimed to evaluate the psychometric properties of a measure of attitudes and subjective norms toward OC use among Korean American women as a first step to determine whether the measure can be used in this population and, potentially, in other Asian ethnic groups. Methods: The sample consisted of 329 Korean immigrant women living in New York City. The theory of reasoned action guided the development of the measure assessing attitudes and norms. Psychometric evaluation included item analysis, internal consistency estimates of reliability, and construct validity (i.e., factorial, discriminant, and predictive). Results: All item-total correlations were above the recommendation of .30. The Cronbach's alpha for the attitudes and subjective norms measure was .88 and .86, respectively. Exploratory factor analyses revealed four interpretable factors, and confirmatory factor analyses confirmed that the factor structures derived from the exploratory factor analyses fit the data well. Discriminant and predictive validity of the measure were also established. Conclusions: The study provides support for the validity and reliability of the measure and its use for determining the degree to which Korean immigrant women intend to use OCs.